Successful treatment of severe COVID‐19 pneumonia in a liver transplant recipient. Issue 7 (19th April 2020) - Liu, Bin; Wang, Yangzhong; Zhao, Yuanyuan; Shi, Huibo; Zeng, Fanjun; Chen, Zhishui
Abstract : Coronavirus disease 2019 (COVID‐19) pandemic spreads rapidly and may be an increasing challenge for transplant community. Clinical data on COVID‐19 infection in transplant population is very limited. Herein we presented the clinical course and outcome of a 50‐year‐old male post liver transplantation who contracted COVID‐19, with subsequent infection of his wife. The process of illness was representative. A therapeutic regime with temporary immunosuppression withdrawal and systemic low‐dose corticosteroid as principle was involved in the management of the patient which made him recover from severe COVID‐19 pneumonia. Abstract : The authors present the marked characteristics and therapeutic interventions on a liver transplant recipient with severe COVID‐19 pneumonia and reveal that temporal immunosuppression withdrawal and low‐dose steroids might be rewarding for recovery of this immunocompromised patient.